Predictive value of abdominal wall scar score for pelvic floor function rehabilitation, vaginal microecology and complications after cesarean section - Yang,Yanhong; Yang,Hailan; Ji,Jingru; Zhao,Ye; He,Yinfang; Wu,Junyan (PeerJ, 2023)
Objective To explore the predictive value of the abdominal wall scar score for pelvic floor function rehabilitation, vaginal microecology and complications after cesarean section. Methods A total of 120 pregnant women who underwent cesarean section in our hospital from January to December 2022 were selected. The patients were divided into observation group (score ≥ 60, n = 52) and control group (score < 60, n = 68) according to the preoperative score of abdominal wall scar and whether the score exceeded 60. The pelvic floor function rehabilitation, vaginal microecology and complications were compared between the two groups, and the score of abdominal wall scar was evaluated by receiver operating characteristic (ROC) curve. The predictive value of pelvic floor function rehabilitation, vaginal microecology and complications after cesarean section was evaluated. Results There were significant differences between the two groups in postpartum class I and class II muscle fiber strength and pelvic floor muscle potential (P < 0.05). ROC curve showed that the AUC of abdominal scar score in predicting pelvic floor function rehabilitation was 0.806 (95% CI [0.684–0.927]), the specificity was 80.17%, and the sensitivity was 79.76%. There was significant difference in the abnormal rate of leukocte estrase (LE) and Acetylaminoglucosidase (NAG) between the two groups (P < 0.05). ROC curve showed that the AUC of abdominal scar score in predicting vaginal microecology was 0.871 (95% CI [0.776–0.966]), the specificity was 85.09%, and the sensitivity was 82.36%. There was significant difference in the incidence of postpartum complications between the two groups (P < 0.05). ROC curve showed that the AUC of abdominal scar score in predicting complications was 0.844 (95% CI [0.735–0.953]), the specificity was 82.27%, and the sensitivity was 81.15%. Conclusion The abdominal scar score has a certain effect on predicting the recovery of pelvic floor function, vaginal microecology and complications after cesarean section. Therefore, it can help the medical staff to adjust the treatment measures in time, which can be used as a means of preoperative auxiliary examination.
Keywords: Abdominal wall scar score; After cesarean section again; Rehabilitation of pelvic floor function; Vaginal microecology; Complications; Predictive value